Radiotherapy combined with chemotherapy increases the risk of herpes zoster in patients with gynecological cancers: a nationwide cohort study - Lee, Peng-Yi (J Gynecol Oncol, 2020)
OBJECTIVE: This study aimed to determine the effect of radiotherapy (RT) on the risk of herpes zoster (HZ) in patients with gynecological cancers via a nationwide population-based study. METHODS: Based on patient data obtained from the National Health Insurance Research Database, 1928 gynecological cancer patients were identified with 1:1 matching for RT and non-RT cohorts by age, index date, and cancer type. Another cohort consisting of 964 non-cancer individuals matched was used as normal control. The incidence of HZ was compared between cancer patients with and without RT. Age, comorbidities, cancer-related surgery and chemotherapy (CT), and cancer type were adjusted as confounders. RESULTS: The risk of HZ in cancer patients was higher than that of non-cancer individuals (14.23 versus 8.34 per 1,000 person-years [PY], the adjusted hazard ratio [aHR]=1.38, p=0.044). In the cancer population, the incidence of HZ for the RT and non-RT cohorts was 20.55 versus 10.23 per 1,000 PY, respectively (aHR=1.68, p=0.009). Age >50 years was an independent factor for developing HZ. The 5-year actuarial incidence for patients receiving neither RT nor CT, RT alone, CT alone, and combined modalities was 5.4%, 6.9%, 3.7%, and 9.9%, respectively (p<0.001). In the RT cohort, the risk rose rapidly in the first year, becoming steady thereafter. CONCLUSION: This population-based study showed that gynecological cancer patients receiving RT combined with CT had the highest cumulative risk of HZ. Health care professionals should be aware of the potential toxicities.